2022
DOI: 10.3390/v15010010
|View full text |Cite
|
Sign up to set email alerts
|

Only Subclinical Alterations in the Haemostatic System of People with Diabetes after COVID-19 Vaccination

Abstract: People with diabetes have an increased risk of experiencing adverse COVID-19 outcomes. COVID-19 vaccination is, therefore, highly recommended. However, people with diabetes have an inherently elevated risk of thrombotic events and the impact of the vaccination on the coagulation system in this patient population remains to be elucidated. The aim of this study was to investigate the impact of COVID-19 vaccination on the haemostatic system in people with type 1 or type 2 diabetes. We evaluated the effects of COV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Finally, a recent prospective cohort study conducted in the USA confirmed these findings and further showed that T1DM patients had a higher risk of hospitalization for COVID-19 than T2DM patients [57]. It should not be neglected that SARS-CoV-2 patients with diabetes are more prone to the development of severe clinical presentation [58,59], as well as the complicated course of the disease, especially when they are not regulated properly. A large prospective cohort study that included 9058 patients in Romania showed that patients with T2DM were associated with higher intensive care unit mortality [60].…”
Section: Covid-19 and Diabetes Mellitusmentioning
confidence: 70%
See 1 more Smart Citation
“…Finally, a recent prospective cohort study conducted in the USA confirmed these findings and further showed that T1DM patients had a higher risk of hospitalization for COVID-19 than T2DM patients [57]. It should not be neglected that SARS-CoV-2 patients with diabetes are more prone to the development of severe clinical presentation [58,59], as well as the complicated course of the disease, especially when they are not regulated properly. A large prospective cohort study that included 9058 patients in Romania showed that patients with T2DM were associated with higher intensive care unit mortality [60].…”
Section: Covid-19 and Diabetes Mellitusmentioning
confidence: 70%
“…Furthermore, there are reports about more frequent adverse reactions to the vaccines with diabetic patients [118,119], but other researchers did not find such a relation [58]. There were concerns that, since diabetes mellitus is a procoagulatory state, vaccines could precipitate thromboembolic incidents, but a study investigating coagulation pathways in T1DM and T2DM patients after vaccination did not find significant differences compared to healthy individuals [59]. Vaccines not only reduce the chance of severe clinical presentation and hospital admission in diabetic patients [120] but could also have a protective effect and reduce the possibility of developing diabetes mellitus after COVID-19 in healthy individuals [108,121].…”
Section: Covid-19-vaccine-induced Diabetes Mellitusmentioning
confidence: 99%